Promotional Efforts by Government and Impact on Purchase Intention of Ayurvedic Products (International Journal of Food and Nutritional Sciences, 2022)
The increasing global shift toward natural and holistic wellness solutions has significantly boosted the demand for Ayurvedic products. Governmental interventions play a crucial role in influencing consumer behavior and enhancing purchase intentions through strategic promotional efforts